What happens at night? Physiological mechanisms related to maintaining grain yield under high night temperature in rice. (25th March 2021) - Xu, Jiemeng; Misra, Gopal; Sreenivasulu, Nese; Henry, Amelia
Abstract: High night temperature (HNT) causes substantial yield loss in rice ( Oryza sativa L.). In this study, the physiological processes related to flag leaf dark respiration (Rn) and grain filling under HNT were explored in a multi‐parent advanced generation intercross population developed for heat tolerance (MAGIC heat ) along with selected high temperature tolerant breeding lines developed with heat‐tolerant parents. Within a subset of lines, flag leaf Rn under HNT treatment was related to lower spikelet number per panicle and thus reduced yield. HNT enhanced the nighttime reduction of non‐structural carbohydrates (NSC) in stem tissue, but not in leaves, and stem nighttime NSC reduction was negatively correlated with yield. Between heading and harvest, the major difference in NSC concentration was found for starch, but not for soluble sugar. HNT weakened the relationship between NSC remobilization and harvest index at both the phenotypic and genetic level. By using genome‐wide association studies, an invertase inhibitor, MADS box transcription factors and a UDP‐glycosyltransferase that were identified as candidate genes orchestrating stem NSC remobilization in the control treatment were lost under HNT. With the identification of physiological and genetic components related to rice HNT response, this study offers promising prebreeding materials and trait targets to sustain yield stability under climate change. Abstract : Physiological response to high night temperature (HNT) was explored in rice ( Oryza sativa L.) heat prebreeding lines. In stems, nighttime reduction of non‐structural carbohydrates, as well as starch remobilization between heading and harvest, was affected by HNT and correlated with yield.